Study guides

☆☆

Q: What is the derivative of square root of 2?

Write your answer...

Submit

Still have questions?

Related questions

The derivative of sqrt(2) is zero.

Use the formula for the derivative of a power. The square root of (x-5) is the same as (x-5)1/2.

The derivative of cos x is -sin x, the derivative of square root of x is 1/(2 root(x)). Applying the chain rule, the derivative of cos root(x) is -sin x times 1/(2 root(x)), or - sin x / (2 root x).

The square root of x = x to the power of a half

If you mean:f(x) = x1 + root(2)The derivative of x1, or x, is simply 1. The derivative of the square root of 2, just like the derivative of any constant, is zero. Therefore, the derivative of the entire function is one.If you mean:f(x) = x1 + root(2)you shuld use the power rule (the exponent, multiplied by x to the power (exponent minus 1)):(1 + root(2)) xroot(2)If you mean:f(x) = x1 + root(2)The derivative of x1, or x, is simply 1. The derivative of the square root of 2, just like the derivative of any constant, is zero. Therefore, the derivative of the entire function is one.If you mean:f(x) = x1 + root(2)you shuld use the power rule (the exponent, multiplied by x to the power (exponent minus 1)):(1 + root(2)) xroot(2)If you mean:f(x) = x1 + root(2)The derivative of x1, or x, is simply 1. The derivative of the square root of 2, just like the derivative of any constant, is zero. Therefore, the derivative of the entire function is one.If you mean:f(x) = x1 + root(2)you shuld use the power rule (the exponent, multiplied by x to the power (exponent minus 1)):(1 + root(2)) xroot(2)If you mean:f(x) = x1 + root(2)The derivative of x1, or x, is simply 1. The derivative of the square root of 2, just like the derivative of any constant, is zero. Therefore, the derivative of the entire function is one.If you mean:f(x) = x1 + root(2)you shuld use the power rule (the exponent, multiplied by x to the power (exponent minus 1)):(1 + root(2)) xroot(2)

7/2 t^5/2^

The derivative of any constant - any expression that does not involve the independent variable - is zero.

the anti-derivative for 2^(1/2) is 2^(1/2)x

-1/(2*x2)

Write square root of x as x1/2. Then use the formula for the derivative of a power.

Derivative with respect to 'x' of (5x)1/2 = (1/2) (5x)-1/2 (5) = 2.5/sqrt(5x)

3/(4*square root(x)) ....Mukesh

-1/2*x-3/2 which is equal to -1/[2*x3/2]

sqrt(x) = x^(1/2) The derivative is (1 / 2) * x^(-1 / 2) = 1 / (2 * x^(1 / 2)) = 1 / (2 * sqrt(x))

y = square root of x y = x(1/2) y' = (1/2)x(1/2 - 1) y' = (1/2)x(-1/2) y' = (1/2)(square root of x)

So basically this is just a quotient rule problem with the chain rule Turn the square root into the 1/2 power and the derivative of the bottom with the chain rule is 1/2(1+x^2)^-1/2 and add on the derivative of the inside, 2x the full derivative is ((1+x^2)(1)-(x)(1/2(1+x^2)^-1/2 +2x))/ 1+x^2 since you square the denominator when you apply the quotient rule.

3

y=(8x).5 + (4x).5 = (2+2sqrt(2))x.5 y'=(1 + sqrt(2))/sqrt(x)

The square root of 2 plus the square root of 2 is equal to twice the square root of 2, therefore the correct answer is: 2(√2) or √8

2.5

The derivative of ( x1/2 ) with respect to 'x' is [ 1/2 x-1/2 ], or 1/[2sqrt(x)] .

The derivative, with respect to x, is -x/sqrt(1-x2)

2 square root 2

x*x1/2= x3/2 Derivative = 3/2 * x1/2

4